A Comparative Socio-Economic Study of Bugis Fishermen In Wajo Regency And In Merauke Regency - Putri, Harmin Adijaya; Sajriawati, Sajriawati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Bugis fishermen are known as accomplished sailors. Most Bugis people live from fishing and maritime trade, which generally depend wholly or largely on the use of aquatic resources for their economic life. This research aims to compare the socio-economic conditions of fishermen in Wajo Regency and Bugis fishermen who migrate to Merauke Regency. The research was conducted for 3 months, namely from December 2023 to February 2024 with a quantitative approach. The research locations are in Wajo Regency, South Sulawesi Province and in Merauke Regency, South Papua Province. The results of the research show that Bugis fishermen in Wajo Regency carry out activities to utilize and manage aquatic resources in the waters of Tempe Lake using nets and barges (fishing nets and barges), while Bugis fishermen in Merauke Regency carry out activities to utilize and manage aquatic resources on the Lampu Satu coastal, using the Semang boat with drift gillnet fishing gear. The fishing facilities used by Bugis fishermen in Wajo Regency are the Fish Auction Place, while Bugis fishermen in Merauke Regency use the Archipelago Fishing Port facilities. The shape of Bugis fishermen's houses in both Wajo Regency and Merauke Regency both have the characteristics of traditional Bugis houses, namely they are made of wood and have poles. The local wisdom of Bugis fishermen in Wajo Regency, such as the Maccera Tappareng activity, also holds boat races and Mappadendang events, while the local wisdom of Bugis fishermen in Merauke Regency is the Barzanji activity. LoA, Kor